FES100 : Basic sampling / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course covers basic sewing technique and clothing components. Students will be introduced to common rules of workshop rules, operating sewing equipment, basic sewing technique and finishing.